Ethnic Identity as a Predictor of Microaggressions Toward Blacks, Whites, and Hispanic LGBs by Blacks, Whites, and Hispanics. Issue 1 (2nd January 2017) - Elias, Troy; Jaisle, Alyssa; Morton-Padovano, Cynthia
ABSTRACT: Results of the study suggest racial differences still exist when it comes to attitudes toward homosexuality in the United States. Findings indicate Black individuals hold significantly less favorable attitudes toward lesbian/gay/bisexual (LGB) individuals than non-Hispanic White individuals but not Hispanics, after controlling for demographics. Hispanic individuals' attitudes toward LGBs were not significantly different from those of non-Hispanic Whites. Despite less favorable attitudes toward LGBs, however, Black Americans display a significantly lower likelihood of engaging in LGB-directed microaggressions than both non-Hispanic Whites and Hispanics. Finally, the results of the study indicate that as non-Hispanic White individuals' ethnic identity gets stronger, their likelihood of engaging in microaggressions toward LGBs increases, more so than Black or Hispanic individuals.